Anti-HIV Aptamers: Challenges and Prospects - Serumula, William; Fernandez, Geronimo; Gonzalez, Victor M.; Parboosing, Raveen (Current HIV Research, 2022)
Human Immunodeficiency Virus (HIV) infection continues to be a significant health burden in many countries around the world. Current HIV treatment through a combination of different antiretroviral drugs (cART) effectively suppresses viral replication, but drug resistance and crossresistance are significant challenges. This has prompted the search for novel targets and agents, such as nucleic acid aptamers. Nucleic acid aptamers are oligonucleotides that attach to the target sites with high affinity and specificity. This review provides a target-by-target account of research into anti-HIV aptamers and summarises the challenges and prospects of this therapeutic strategy, specifically in the unique context of HIV infection.
Keywords: treatment